PENGARUH LITERASI KEUANGAN SYARIAH, PERILAKU KEUANGAN DAN AKTIVITAS MEDIA SOSIAL TERHADAP MINAT INVESTASI GENERASI Z DI KOTA JAMBI - Najla Syifa Syauqiah Azell; Nurlia Fusfita (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
The increasing interest of young people in investment especially driven by financial technology and social media serves as the main motivation for this research. Generation Z is selected due to their productive age and strong connection with digital platforms, including access to financial and investment information. This research uses a quantitative approach with multiple linear regression analysis. The population in this study is Generation Z in Jambi City aged 20–28 years, with a sample of 140 respondents selected using purposive sampling. Data was collected through a Google Form-based questionnaire and analyzed using SPSS version 26. The results show that, partially, Islamic Financial Literacy and Financial Behavior have no significant effect on Investment Interest. Meanwhile, Social Media Activity has a positive and significant influence. Simultaneously, all three variables significantly affect Investment Interest among Generation Z in Jambi City, with a coefficient of determination (R²) of 42.9%. This indicates that the combination of these variables explains a substantial portion of the variation in respondents’ investment interest.